The Australian judiciary / H P Lee, Enid Campbell. - Lee, H. P., 1947-; Campbell, Enid Mona, 1932- (Cambridge University Press, 2013)
The second edition of H. P. Lee's The Australian Judiciary provides a timely update to this seminal text. The only definitive survey of the entire Australian judiciary, this text describes and evaluates the work, techniques, problems and the future of the different tiers of courts and judges. It discusses the role of the judiciary as the third sector of government and analyses and comments on judicial conduct, judicial independence and impartiality, the work of judges beyond the courts, the accountability of judges and the dangers to judicial institutions. It is an excellent reference work which will appeal to legal scholars and practitioners throughout Australia and internationally.